Modeling Cognitive Process from Visual Attention Geometry in AR/VR: A Machine Learning Approach - Lupascu, Ioana. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Daniel Hannon.; Committee: James Intriligator, and Farakh Zaman.; Keywords: Cognitive psychology, Artificial intelligence, and Quantitative psychology.